THE ROLE OF ORGANIZATIONAL CULTURE TO BUILD EMPLOYEE LOYALTY - Eva Noviana; Leonard Adrie Manafe (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research has a purpose for the role of organizational culture in the company to build a loyalty to the employees of the Power Generation Company (PPL) in the city of Sidoarjo. In this study using descriptive qualitative analysis method using data collection techniques chosen by the author in the form of interviews, observations and document studies. The research informants were seven employees of the company. The results of the study show that the role of organizational culture in PPL is able to build employee loyalty through the "AKHLAK" (Amanah, Kompeten, Harmonis, Loyal, Adaptif, dan Kolaboratif) culture, and is balanced with the application of "SIAP" (Service Oriented, Integrity, Active Learning and Professional) corporate values. With this organizational culture, it will unite every employee of the company and can also foster a sense of employee loyalty to the company.